DOX-CONJUGATED HIGH-QUALITY AgZnInS QDs FOR REVERSAL OF MULTIDRUG RESISTANCE - LINGZHI QU; DAWEI DENG; JIE WANG; YUEQING GU (Journal of Innovative Optical Health Sciences, 2014)
The synthesis of water-soluble quantum dots (QDs) has recently received extensive attention due to noninvasive detection of biological information in living subjects. In this paper, high-quality water-soluble (cadmium-free) quaternary AgZnInS QDs have been successfully synthesized using a green synthetic route. The as-prepared QDs exhibit tunable photoluminescence (PL) emission between 521 and 658 nm. Secondly, multidrug resistance (MDR) is a major impediment to the effective cancer chemotherapy. DOX, a widely used antitumor drug was modified on the surface of the QDs in this study. It, therefore, significantly enhanced the cytotoxicity of DOX to MDR cancer cells as the QDs could bring the DOX to nucleus.